B3Ø: Blynk-interfaced Three-Phase Smart Energy Monitoring System - Cubacub, I. K. I.; Caburata, S. N. C.; Calaguas, E. K. L.; De Leon, J. A. M.; Dimaano, M. P.; Dizon, I. F. R.; Dongallo, L. I.; Tangcuangco, A. L.; Parungao, R. L. D. (International Journal of Electrical Engineering and Applied Sciences (IJEEAS), 2025)
This research is focused on the design and evaluation of an installed three-phase smart energy monitoring system with Blynk integration at a state university in the province of Pampanga, Philippines. The main objective of this project was to design a low-cost, precise, and user-friendly solution for the real-time monitoring of electrical parameters in a 230 V three-phase delta transformer bank power distribution system. The system is capable of monitoring voltage, current, power, power factor, and total energy consumption. The prototype’s initial evaluation was done at the distribution utility of Pampanga using a power quality analyzer, and then a field test at the state university, where its performance was compared with the installed utility meter. The test results from different test cases and scenarios indicated that the system possessed a high measurement accuracy, varying within the ANSI C12.1-2008 ±2% threshold. It possessed a low energy measurement error of 0.08% over the testing period. In addition, the system also detected high phase loading imbalances, thus proving its ability to diagnose power distribution inefficiency. Integration of Blynk provides remote monitoring and data visualization, further enhancing its potential in campus energy management. The system was accurate, reliable, and scalable demonstrating itself as a feasible solution for institutional energy monitoring and potential integration into smart grid infrastructures.